2014
DOI: 10.3945/ajcn.114.086322
|View full text |Cite
|
Sign up to set email alerts
|

Use of a concentrated enteral nutrition solution to increase calorie delivery to critically ill patients: a randomized, double-blind, clinical trial

Abstract: Background: Critically ill patients typically receive w60% of estimated calorie requirements. Objectives: We aimed to determine whether the substitution of a 1.5-kcal/mL enteral nutrition solution for a 1.0-kcal/mL solution resulted in greater calorie delivery to critically ill patients and establish the feasibility of conducting a multicenter, double-blind, randomized trial to evaluate the effect of an increased calorie delivery on clinical outcomes. Design: A prospective, randomized, double-blind, parallel-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 34 publications
3
94
3
2
Order By: Relevance
“…Till day 14 or discharge from the ICURice et al, 2011 [15]Acute respiratory failureRCT20053 years in the intervention group, 54 years in the control group4426.9 in both groups100 %Trophic feeding (300 ± 149 kcal; 15.8 ± 11 % of caloric requirement) Protein intake: 0.13 g/kg/dayFull feeding (1418 ± 686 kcal; 74.8 ± 38.5 % of caloric requirement) Protein intake 0.66 g/kg/day6 daysRice et al, 2012 [16] a ARDS patients (medical, surgical and trauma)RCT100052 years in the intervention and control groups51APACHE III: 92 in the intervention group, 90 in the control group100 %Trophic feeding (400 kcal; 25 % of estimated non-protein caloric requirement)Full feeding (1300 kcal; 80 % of estimated caloric requirement)6 daysHuang et al, 2012 [64]MedicalRCT10170.9 years in the intervention group, 68.3 years in the control group7121.0 in the intervention group, 19.6 in the control group100 %Nasoduodenal feeding (1575 kcal; 90.4 % of target energy intake). Protein intake 93.2 ± 26.9 % of targetNasogastric feeding (1343 kcal; 76.2 % of target energy intake) Protein intake 78.6 ± 28.5 % of target21 daysReignier et al, 2013 [65] a Medical and surgicalRCT44961 years in the intervention group, 62 years in the control group70Baseline SOFA 8 for both groups100 %Not monitoring residual gastric volume (calorie deficit 319 kcal)Monitoring residual gastric volume (calorie deficit 509 kcal)Not clear Follow up for 90 daysRugeles et al, 2013 [23]Medical and surgicalRCT8053.3 years in the intervention group, 55.7 years in the control group5813.9 in the intervention group, 15.1 in the control groupHyperproteic hypocaloric enteral nutrition as 15 kcal/kg/day (756 kcal) Protein intake 1.4 g/kg/dayStandard nutritional regimen as 25 kcal/kg/day (921 kcal) Protein intake 0.76 g/kg/day7 daysPeake et al, 2014 [66]Mechanically ventilated (medical and surgical)RCT11256.4 years in the intervention group, 56.5 years in the control group7423 in the intervention group, 22 in the control group100 %Nutritional formula 1.5 kcal/ml (1832 ± 381 kcal; 27.3 ± 7.4 kcal/kg; 96.0 % of requirement) Protein intake 75 % of targetNutritional formula 1 kcal/ml (1259 ± 428 kcal; 19.0 ± 6.0 kcal/kg; 68.4 % of requirement) Protein intake 79 % of target10 daysCharles et al,...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Till day 14 or discharge from the ICURice et al, 2011 [15]Acute respiratory failureRCT20053 years in the intervention group, 54 years in the control group4426.9 in both groups100 %Trophic feeding (300 ± 149 kcal; 15.8 ± 11 % of caloric requirement) Protein intake: 0.13 g/kg/dayFull feeding (1418 ± 686 kcal; 74.8 ± 38.5 % of caloric requirement) Protein intake 0.66 g/kg/day6 daysRice et al, 2012 [16] a ARDS patients (medical, surgical and trauma)RCT100052 years in the intervention and control groups51APACHE III: 92 in the intervention group, 90 in the control group100 %Trophic feeding (400 kcal; 25 % of estimated non-protein caloric requirement)Full feeding (1300 kcal; 80 % of estimated caloric requirement)6 daysHuang et al, 2012 [64]MedicalRCT10170.9 years in the intervention group, 68.3 years in the control group7121.0 in the intervention group, 19.6 in the control group100 %Nasoduodenal feeding (1575 kcal; 90.4 % of target energy intake). Protein intake 93.2 ± 26.9 % of targetNasogastric feeding (1343 kcal; 76.2 % of target energy intake) Protein intake 78.6 ± 28.5 % of target21 daysReignier et al, 2013 [65] a Medical and surgicalRCT44961 years in the intervention group, 62 years in the control group70Baseline SOFA 8 for both groups100 %Not monitoring residual gastric volume (calorie deficit 319 kcal)Monitoring residual gastric volume (calorie deficit 509 kcal)Not clear Follow up for 90 daysRugeles et al, 2013 [23]Medical and surgicalRCT8053.3 years in the intervention group, 55.7 years in the control group5813.9 in the intervention group, 15.1 in the control groupHyperproteic hypocaloric enteral nutrition as 15 kcal/kg/day (756 kcal) Protein intake 1.4 g/kg/dayStandard nutritional regimen as 25 kcal/kg/day (921 kcal) Protein intake 0.76 g/kg/day7 daysPeake et al, 2014 [66]Mechanically ventilated (medical and surgical)RCT11256.4 years in the intervention group, 56.5 years in the control group7423 in the intervention group, 22 in the control group100 %Nutritional formula 1.5 kcal/ml (1832 ± 381 kcal; 27.3 ± 7.4 kcal/kg; 96.0 % of requirement) Protein intake 75 % of targetNutritional formula 1 kcal/ml (1259 ± 428 kcal; 19.0 ± 6.0 kcal/kg; 68.4 % of requirement) Protein intake 79 % of target10 daysCharles et al,...…”
Section: Resultsmentioning
confidence: 99%
“…All except two studies [57, 66] were un-blinded. Agreement between reviewers (kappa) on the tool elements was 0.774 (95 % CI 0.651–0.892; p  < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In year 2014, Peake et al 36 randomized patients to receive isonitrogenous enteral formula with caloric density 1.5 kcal/ml and 1.0 kcal/ml. It was found that the 1.5 kcal/ml group who received significantly more calories had trend toward improved duration of survival (p=0.057), although there was no difference on VFD to day-28 and ICU & hospital length of stay.…”
Section: Randomized Controlled Trial (Rct)mentioning
confidence: 99%